Electrical power transmission and distribution : aging and life extension techniques - Chudnovsky, Bella H. (CRC Press, 2013)
"Preface Every transmission and distribution apparatus is a complex engineering system of electrical and mechanical components made of various conductive and insulating materials. When in service, these systems are exposed to multiple environmental stresses (atmospheric corrosive gases, contaminants, high and low temperatures); mechanical stresses (vibrations, shocks, handling); electrical stresses and electrostatic discharges and many other internal and external impacts. The effect of stresses is cumulative, leading to progressive damage and significant deterioration (aging) of the electrical systems. Continuous aging sooner or later results in a decreased or destroyed ability of the electrical apparatus to function properly and safely. A thorough analysis of the factors that accelerate aging and cause the failure of various materials in electrical apparatus allows to suggest multiple techniques for diminishing the impact of deteriorating factors, thus preventing a premature failure. Various aging-mitigating procedures extending the life of the electrical equipment have emerged and became available. The author's purpose is to help find proper ways to slow down the aging of electrical apparatus, improve its performance, and extend the life of power transmission and distribution equipment. This book is designed to serve as a reference manual for engineering, maintenance, and training personnel to aid in understanding the causes of equipment deterioration. Under one cover, it makes available extensive information, which is very hard to obtain since it is scattered among many different sources such as manufacturers documentation, journal papers, conference proceedings, and general books on plating, lubrication, insulation, and so on"--